THE EFFECT OF PEANUT SEEDLING DENSITY AND BIOGUTTEN APPLICATION ON SOIL BULK DENSITY IN SOILS PRONE TO IRRIGATION EROSION. - Jo’raev Akmaljon Normukhamadovich; Mo’minjonov Sanjarbek Ravshanbek o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses the results of field trials conducted to determine the soil volume loss of peanut seedlings and the criteria for using the biological preparation Biogutten in its cultivation.